The extraction of orthosiphon stamineus using hydro distillation method - Mohd Najib, Razali (2006)
Orthosiphon Stamineus (Misai Kucing) produce essential oil which is important in medicine. Entrepreneur and researcher nowadays use steams distillation method to extract Orthosiphon Stamineus essential oil. The objective of this study is to obtain essential oil from Orthosiphon Stamineus plant source using hydro distillation technique. Rotary evaporator was used to extract the essential oil. Effects of time and particle size parameters were studied in order to have higher yield. The temperature and pressure for the extraction process were set at 100oC and 1 bar respectively. The obtained result showed that optimum time was 12 hours. Longer time operation and smaller particles size proved that higher yield was obtained. The presence of either one these compositions, Eupatorin (EUP), Sinensetin (SEN), Rosmarinic Acid (RA) and 3hydroxy-5,6,7,4-tetramethoxyflavone (TMF) should take as a characteristic for Orthosiphon Stamineus essential oil was studied as well. The essential oil was analyzed using High Performance Liquid Chromatography (HPLC). The analyzed using HPLC showed that the Rosmarinic Acid was obtained in Orthosiphon Stamineus extracted via hydro distillation method.